Development of a Quantitative PCR Method for Specific and Quantitative Detection of Enterocytospora artemiae, a Microsporidian Parasite of Chinese Grass Shrimp (Palaemonetes sinensis) - Jiang, Hongbo; Bao, Jie; Liu, Jinghui; Chen, Yuwen; Feng, Chengcheng; Li, Xiaodong; Huang, Shuai; Chen, Qijun (Frontiers in Marine Science, 2021)
Enterocytospora artemiae (EAM) mainly parasitizes the hepatopancreas of Palaemonetes sinensis. Serious infection leads to hepatopancreatic lesions, which greatly reduce the vitality of P. sinensis. Currently, EAM is detected via conventional PCR methods. However, conventional PCR has low sensitivity and cannot be used for accurate quantitative detection of EAM or its parasitic activity in host tissues. In this study, we designed a pair of specific primers based on the sequence of the ribosomal protein S9 gene (RPS9; GenBank accession number: MZ420734) to establish and optimize a SYBR Green I real-time fluorescent quantitative PCR detection method for EAM. Only EAM appeared as a bright and single target band, whereas other microorganisms did not, indicating that the primer for RPS9 had high specificity. This method displayed optimum amplification effects at an annealing temperature of 55°C, and the melting curve of the product produced a single peak. The established method showed a good linear relationship from 2.2 × 108 to 2.2 × 101 copies/μL. The relationship between the number of cycle thresholds (Ct) and the logarithm of the initial template amount (x) conformed to Ct = −3.281 log x + 36.543 (R2 = 0.998). Amplification efficiency was 101.737%, and the lower limit of detection sensitivity was 2.2 × 101 copies/μL. Good intra- and inter-group repeatability was observed within the linear range. The sensitivity of this method was more than 200 times higher than that of nested PCR. Thus, detection data obtained using this method may be useful as a technical reference for rapid and accurate identification of EAM infection and for the prevention and control of EAM during P. sinensis breeding.